Fields - Robert M. Arens (Oz, 1999)
The Fields Project was an inquiry into spatial transformation through the means of construction. Several spaces along the east entry sequence to Kansas State University’s Seaton Hall were appropriated as the sites of simple but strong installations meant to activate the sequence and transform the perception of persons who move daily through the banal spatial configuration. Ed. note: Three installations constructed by Professor Robert Arens with assistance from a group of students.